2013
DOI: 10.1016/j.jtcvs.2012.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for secondary pneumothorax in patients aged more than 80 years

Abstract: 2 ; however, the addition of balloon occlusion of the outflow graft allowed controlled exchange of the device without the need to surgically control and clamp the graft, 3 reducing surgical dissection and potential morbidity. Placement of a Foley catheter into the outflow graft 4 offers another option of controlling back bleeding from the aorta; however, connecting the outflow graft to the new device can be made difficult by uncontrolled bleeding because the Foley catheter must be removed. Furthermore, deairi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Therefore, in recent years, age alone has not been used as a criterion for any type of surgery for SSP. Several studies have shown favorable outcomes by applying the surgical principle of minimal repair in elderly patients with SSP (20,21,23,24). Surgeries following this principle aim to excise only the targeted, active leakage point, and avoid performing a bullectomy of thick-walled bullae or a lung-volume-reduction surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in recent years, age alone has not been used as a criterion for any type of surgery for SSP. Several studies have shown favorable outcomes by applying the surgical principle of minimal repair in elderly patients with SSP (20,21,23,24). Surgeries following this principle aim to excise only the targeted, active leakage point, and avoid performing a bullectomy of thick-walled bullae or a lung-volume-reduction surgery.…”
Section: Discussionmentioning
confidence: 99%